Multilingual Names on the Finnish Basic Map - Leino, Antti (York University, 2009)
The <Finnish Basic Map> and the computerised maintained by the National Land Survey for map-making purposes have place names in five different languages: the official Finnish and Swedish, and three semi-official Sámi languages. As one would expect, distributions of the various languages overlap, and roughly one percent of the named places have names in more than one language. All five naming systems are similar enough that semantically transparent toponyms can be translated from one language to another. The three Sámi languages are also similar enough that virtually all common multilingual names are also common in each of their respective languages. This is also true for Finnish and Swedish, but the names common to Finnish and the Sámi languages often involve elements that have a more limited geographic distribution in Finnish. All this gives some insight into the underlying cultural interplay, and also into the role of semantic transparency in name use.